Ma’naviyatning yurtimiz hayotida dolzarbligi - Berkinov Oybek Toxir o’g’li, Sherniyazov Sherzod Qurbonniyazovich, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
The Uzbek people paid special attention to the education of young people in their culture and spirituality, and the cultivation of such levels of perfection was considered important in every era. Hazrat Navoi also said: "If you say that you will pass away without sorrow, you have learned knowledge and skills." Leaving the world without maturity is the same as coming out of the bathroom without being clean. So, the desire to come into the world is to strive for perfection and goodness. Every nation dream of seeing perfection in its future generation. Such human qualities are formed in the family. The health of the spiritual and moral environment in the society, the education of a perfect person depends to a large extent on family culture and upbringing. As the family is, so is the society. The future of our country, the tomorrow of our people, the reputation of our country in the world community, depends, first of all, on how our children will grow up and become human beings. We should never forget such a sharp truth.